2003
DOI: 10.2337/diabetes.52.2.365
|View full text |Cite
|
Sign up to set email alerts
|

Role of Endogenous Glucagon-Like Peptide-1 in Islet Regeneration After Partial Pancreatectomy

Abstract: A reduction in ␤-cell mass is an important causative factor in type 1 and type 2 diabetes. Glucagon-like peptide-1 (GLP-1) and the long-acting agonist exendin 4 (Ex-4) expand ␤-cell mass by stimulating neogenesis and proliferation. In the partial pancreatectomy (Ppx) model, exogenous Ex-4 promotes islet regeneration, leading to sustained improvement in glucose tolerance. In this study, we investigate the potential role of endogenous GLP-1 in islet growth. We examined ␤-cell mass regeneration after 70% Ppx in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
113
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(122 citation statements)
references
References 46 publications
9
113
0
Order By: Relevance
“…[22][23][24][25] A recent study in pigs showed increased islet number and β-cell proliferation after RYGBP, in parallel with a rise in GLP-1, demonstrating the effect of RYGBP on the plasticity of the endocrine pancreas in this animal model. 43 Whether this is true in humans is unknown.…”
Section: Rygbp Alters Incretin Physiology Rygbp Enhances Incretin Relmentioning
confidence: 73%
See 1 more Smart Citation
“…[22][23][24][25] A recent study in pigs showed increased islet number and β-cell proliferation after RYGBP, in parallel with a rise in GLP-1, demonstrating the effect of RYGBP on the plasticity of the endocrine pancreas in this animal model. 43 Whether this is true in humans is unknown.…”
Section: Rygbp Alters Incretin Physiology Rygbp Enhances Incretin Relmentioning
confidence: 73%
“…21 Both GLP-1 and GIP have a trophic effect on the β-cell, as demonstrated in vitro and in vivo in rodent studies. [22][23][24][25] GLP-1 has other important physiological effects, including potentiation of GSIS in the post-prandial setting, suppression of glucagon, slowing of gastric emptying, decrease of body weight and favorable cardiovascular protection, 1,26 that makes it an attractive tool for the treatment of overweight or obese individuals with diabetes. The half-life of GLP-1 and GIP is only few minutes and both incretins are rapidly inactivated by the enzyme dipeptidyl peptidase 4 (DPP-4).…”
Section: Importance Of the Incretin Effect In Physiologymentioning
confidence: 99%
“…For example, GLP-1 increased beta-cell mass when injected into C57Bl/6 and db/db mice [18,20], but overexpression of exendin-4 in C57BL/6×SJL mice had no effect on islet size [50]. Moreover, antagonist-mediated prevention of GLP-1 action does not affect islet mass in Balb/c mice, although islet growth and topography are abnormal in GLP-1 receptor null CD1 mice [51,52].…”
Section: Discussionmentioning
confidence: 99%
“…Regeneration was impaired in the GLP-1R −/− mice (De Leon et al, 2003) ZDF fa/fa rats 60% Partially pancreatectomized…”
Section: % Partial Pancreatectomy Balb/c Mice and Glp-1r −/−mentioning
confidence: 99%